Cardiac Gated Computed Tomography Angiography Discloses a Correlation Between the Volumes of All Four Cardiac Chambers and Heart Rate in Men But Not in Women - Tamar Shalmon; Yaron Arbel; Yoav Granot; Tomer Ziv-Baran; Ehud Chorin; Haim Shmilovich; Ofer Havakuk; Shlomo Berliner; Montserrat Carrillo Estrada; Galit Aviram (Mary Ann Liebert, 2020)
Background: Currently, normal values of the cardiac chambers' volumes are adjusted only for gender and body surface area (BSA). We aim to investigate the association between the heart rate and the volume of each of the four cardiac chambers using cardiac-gated computed tomography angiography (CCTA). Methods: A total of 350 consecutive patients without known cardiac diseases or significant (>50%) stenosis undergoing CCTA between January 2009 and June 2014 for suspected coronary artery disease were included. Cardiac chamber volumes adjusted to BSA were calculated using automated model-based segmentation analysis software of the CCTA data and correlated with patients' mean heart rate during the scan. Results: There were 240 men and 110 women, median interquartile range age was 55 years (47?61). Women were older 59.0 years (53.7?64) versus 52.0 years (45.0?59.0), had higher prevalence of hyperlipidemia, diabetes mellitus, anemia, and hypothyroidism, and higher median heart rates 64.0 (59.7?66.0) versus 60.0 (55.0?65.0) (p?<?0.001). Men had a negative correlation between the volume of each cardiac chamber and the heart rate [rage_adj?=?(?0.4)?(?0.27), p?<?0.001 for all], whereas such a correlation was not found in women. The multivariate analysis showed that a decrease of five beats per minute was associated with an increase of 4%?5% in volume of each chamber in men. There was no such association among females. Conclusions: Lower heart rate is associated with an increase of each cardiac chamber volume by CCTA in men. This association is not found in women. More extensive studies are required to further elaborate on these gender differences.